2015
DOI: 10.3390/lubricants3020281
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamic Response of an Unbalanced Flexible Rotor Supported by Elastic Bearings Lubricated with Piezo-Viscous Polar Fluids

Abstract: Abstract:On the basis of the V. K. Stokes micro-continuum theory, the effects of couple stresses on the nonlinear dynamic response of the unbalanced Jeffcott's flexible rotor supported by layered hydrodynamic journal bearings is presented in this paper. A nonlinear transient modified Reynolds' equation is derived and discretized by the finite element method to obtain the fluid-film pressure field as well as the film thickness by means of the implicit Euler method. The nonlinear orbits of the rotor center are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Owing to its relative mathematical simplicity, the couple‐stress fluid model has been widely applied to analyse various hydrodynamic as well as thermo‐hydrodynamic lubrication problems . The theoretical results obtained showed that the presence of the couple stress provides an enhancement of the steady‐state and dynamic characteristics of liquid‐lubricated journal bearings when compared with the Newtonian lubricant case.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its relative mathematical simplicity, the couple‐stress fluid model has been widely applied to analyse various hydrodynamic as well as thermo‐hydrodynamic lubrication problems . The theoretical results obtained showed that the presence of the couple stress provides an enhancement of the steady‐state and dynamic characteristics of liquid‐lubricated journal bearings when compared with the Newtonian lubricant case.…”
Section: Introductionmentioning
confidence: 99%